DAMPAK SOCIAL CAPITAL STRONG-TIES VS WEAK-TIES TERHADAP DEFAULT PEMBIAYAAN INDIVIDU - ALFI SYUKRI RAMA; DAVY HENDRI (Prodi Manaj. Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam – UIN Imam Bonjol Padang, 2018)
LKMS with unique characteristics, in general has the potential to attract risk-averting individuals to access it. This is at least a mechanism of natural selection intervention (ex-ante) in reducing the possibility of adverse selection of customers with the concept of LKMS. However, several studies have also found that various LKMS financing products also provide incentives and disincentives to the trend of stalled installment financing. This study highlights the impact of characteristics such as: risk and religiosity preferences, which may differ from individual beneficiaries of financing in Islamic microfinance institutions (LKMS) against the probability of defaulting their defaults. The study was conducted by taking primary data in the form of samples of 60 customers who received financing from 1 (one) LKMS but consisted of 30 debtors who experienced financing installment defaults and 30 went smoothly. The process of collecting data uses a questionnaire containing questions about basic demographics, in addition to questions aimed at raising Islamic risk and religiosity preferences. In addition, the impact of external environmental characteristics is also estimated by using probit regression. Group-based financing, which is one of the objectives of reducing adverse selection, can have the opposite effect. Ineffective group roles for various reasons, contagion can be a trigger for moral hazard for other group members. The study found that in addition to religiosity, as an internal factor, the effectiveness of financing groups as a timely external factor of timely payment compliance also plays an important role.